A review of Forensic Entomology literature in the southwestern United States. Issue 5 (12th August 2021) - Weidner, Lauren M.; Meeds, Andrew W.; Noblesse, Andrew P.; Hans, Krystal R.
Abstract: An extensive literature search pertaining to forensic entomology research was conducted for the southwestern portion of the United States (Arizona, New Mexico, Oklahoma, and Texas), encompassing literature from 1879 through June 2020. While the majority of states (Arizona, Texas, and Oklahoma) had high numbers of topic specific papers (screwworm, development, and American burying beetle, respectively), the main paper topics for this region were arrival/decomposition studies, biodiversity, and myiasis. With 106 papers, Texas's forensic entomology literature output was higher than the three remaining states combined. This review supports the need for developmental studies of forensically relevant insects. This article is categorized under: Forensic Anthropology > Time Since Death Estimation Crime Scene Investigation > Crime Scene Examination Forensic Biology > Forensic Entomology Abstract : Chrysomya rufifacies larvae. This invasive species entered the United States in the 1980s and has become a dominant colonizer of remains in much of the southwest. (Photo credit: Andrew Meeds).